2020
DOI: 10.1093/jisesa/ieaa116
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Phenoloxidase Activity on Survival Is Host Plant Dependent in Virus-Infected Caterpillars

Abstract: An important goal of disease ecology is to understand trophic interactions influencing the host–pathogen relationship. This study focused on the effects of diet and immunity on the outcome of viral infection for the polyphagous butterfly, Vanessa cardui Linnaeus (Lepidoptera: Nymphalidae) (painted lady). Specifically, we aimed to understand the role that larval host plants play when fighting a viral pathogen. Larvae were orally inoculated with the entomopathogenic virus, Junonia coenia densovirus (JcDV) (Parvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Junonia coenia densovirus (hereafter, JcDV) is a non‐enveloped, single‐stranded DNA virus in the family Parvoviridae ( Densovirinae : Lepidopteran protoambidensovirus 1 ). Though first identified in Junonia coenia (Nymphalidae), JcDV is capable of infecting Lepidoptera in the Bombycidae, Erebidae, Noctuidae, and Nymphalidae in a laboratory setting (Mutuel et al, 2010; Resnik & Smilanich, 2020; Rivers & Longworth, 1968). Larvae become infected by JcDV through ingestion of contaminated food, after which viral particles cross the midgut and replicate in tracheae, hemocytes, visceral muscle, and epidermis (Mutuel et al, 2010; Wang et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Junonia coenia densovirus (hereafter, JcDV) is a non‐enveloped, single‐stranded DNA virus in the family Parvoviridae ( Densovirinae : Lepidopteran protoambidensovirus 1 ). Though first identified in Junonia coenia (Nymphalidae), JcDV is capable of infecting Lepidoptera in the Bombycidae, Erebidae, Noctuidae, and Nymphalidae in a laboratory setting (Mutuel et al, 2010; Resnik & Smilanich, 2020; Rivers & Longworth, 1968). Larvae become infected by JcDV through ingestion of contaminated food, after which viral particles cross the midgut and replicate in tracheae, hemocytes, visceral muscle, and epidermis (Mutuel et al, 2010; Wang et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…As diet-mediated variation in development and immunity provided limited explanation, additional research will be necessary to elucidate how A. jatrophae reared on Plantago are able to suppress viral burdens and increase their likelihood of surviving infection. As the specific routes through which the immune response contributes to defence against JcDV are unclear (Muchoney et al, 2022;Resnik & Smilanich, 2020;Smilanich et al, 2018), it is possible that immune parameters that were not measured are enhanced in larvae consuming Plantago. In addition, the role of phytochemistry warrants consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reviews have found complex relationships between host plant diet and immune response in lepidopterans (Lampert, 2012; Singer et al, 2014). In some cases, larval consumption of the novel, low‐quality host plant resulted in a weakened immune response compared to consumption of the typical, high‐quality host plant (Diamond & Kingsolver, 2011; Resnik & Smilanich, 2020). In other cases, consumption of the alternative, lower quality host plant actually resulted in a stronger immune response (Klemola et al, 2007; Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%